Draft Five Year Plan 1978 -83 Police Housing Government of Madhya Pradesh - Planning Commission (Planning Commission, 1978)
Draft Plan 1978-83, Head of Development-Outlays and Expenditure, Police Housing Scheme, Selected Targets and Achievements.
Government of Madhya Pradesh, Planning, Economics and Statistics Department